Rola społecznej odpowiedzialności biznesu w budowaniu konkurencyjności regionu - Wieteska-Rosiak, Beata (Annales. Etyka w Życiu Gospodarczym, 2012)
Today, the concept of Corporate Social Responsibility is more popular in Poland. Under the framework, many companies are taking actions to its stakeholders and the environment. These include building human capital, social capital and innovation. These elements are the immaterial factors of competitiveness of the region. This means that the actors in the CSR contribute to increasing the competitiveness of the region and its competitive advantage. The article discusses the factors of competitiveness and also provides examples of companies that build them.